PENGEMBANGAN SUPERVISI PENDIDIKAN DI SMK. MAMBAUL ULUM BATA-BATA PAMEKASAN(Analisis Implementatif Terhadap Program Pembelajaran PAI) - Abdul Munib; Thola'al Badruh (Universitas Islam Madura, 2018)
The focus of the research core is: 1) Form of development of education supervision, 2) Results of developing education supervision. The forms of education supervision development activities include: a) Maximizing the available potential, b) giving exemplary example, c) Providing freedom for teachers to be creative, d) Making good communication links to all parties, e) Supervising activities are carried out by means of gradually. While the results of the development of education supervision include: a) Principals' ability to organize and foster teachers, motivate and increase morale, uphold discipline, provide consultation, lead discussions, and help solve problems, develop the teaching profession, seek librarianship for teachers, giving teachers the opportunity to compile lesson material as additional books and creating a conducive, active and fun learning atmosphere, b) developing an applicable curriculum, creating an appropriate learning and teaching climate, directing teachers, coordinating teaching staff, providing new educational information, develop appropriate learning programs, develop learning materials with teachers, develop models of teaching and learning with teachers, develop learning aids with teachers, give examples of teaching and learning models, help create schools as cultural centers to develop students like a whole person, c) improve the implementation of curriculum support activities, establish relationships with the school community.